(untitled) - Sonka, Milan (United States of America, 2014)
Provides coverage of the range of topics encountered in the field of image processing and machine vision. This book helps undergraduates, graduates, researchers, and professionals who are looking for a readable reference
Thị giác máy tính - Công nghệ
Keywords: Xử lý ảnh,Computer vision,Image processing